Shackleton Memorial Library, Scott Polar Research Institute, Cambridge England ... - Campbell, Sandy (University of Alberta Library, 2022)
The Shackleton Memorial Library is part of the larger library of the Scott Polar Research Institute. These doors lead into a "friends room" which contains displays and a meeting area. ...